The Ser82 RAGE variant affects lung function and serum RAGE in smokers and sRAGE production in vitro - Miller, Suzanne; Henry, Amanda P.; Hodge, Emily; Kheirallah, Alexander K.; Billington, Charlotte K.; Rimington, Tracy L.; Bhaker, Sangita K.; Obeidat, Ma’en; Melén, Erik; Merid, Simon K.; Swan, Caroline; Gowland, Catherine; et al. (Public Library of Science, 2016)
Introduction